Postoperative myelitis subsequent to cervical spine radiofrequency ablation: a case report - Xu, Cuiyu; Ding, Maoyu; Yang, Yumei; Dong, Chunke; Xu, Xiaolong; Qu, Zhicheng; Guo, Wei; Cao, Ying (Frontiers in Surgery, 2025)
Commonly used minimally invasive treatment for cervical spondylotic diseases, cervical spine radiofrequency ablation (RFA) provides benefits of faster recovery and less trauma. However, data on the monitoring and management of postoperative complications, especially severe adverse events like myelitis, is limited. This case report details a 75-year-old female patient with a medical history of hypertension, cerebral infarction, and hyperlipidemia who subsequently developed myelitis after undergoing cervical spine radiofrequency ablation (RFA). The patient received effective treatment following a sequence of diagnostic and therapeutic measures, highlighting the risk of severe complications and the vital necessity of maintaining rigorous aseptic protocols during the procedure. This report extensively discusses the etiology of myelitis in this patient and explores the direct or indirect role of RFA in the development of myelitis.